Relevance of the 1844 Manuscripts in Marx's thought: Alienation and alienated labor - Romero Reyes, Antonio (2021)
The decade of the 1940s of the 19th century were vital years in the maturation of thought as well as in the intellectual biography of Karl Heinrich Marx. The economic-philosophical Manuscripts of 1844 were part of a great effort to establish a proper and original episteme; and the present work tries precisely to rescue, reassess and reconstitute such manuscripts in the whole of Marx's thought. Attention is focused on the issue of alienation and / or alienated labor, which is approached from various angles: the hard core of the young Marx's social criticism; the Marxian meanings of alienated labor; the foundation of a critical sociology of capitalism; all this within the framework of the same Manuscripts.